2018
DOI: 10.1111/nph.15011
|View full text |Cite
|
Sign up to set email alerts
|

Constraining uncertainty in the timescale of angiosperm evolution and the veracity of a Cretaceous Terrestrial Revolution

Abstract: Summary Through the lens of the fossil record, angiosperm diversification precipitated a Cretaceous Terrestrial Revolution (KTR) in which pollinators, herbivores and predators underwent explosive co‐diversification. Molecular dating studies imply that early angiosperm evolution is not documented in the fossil record. This mismatch remains controversial.We used a Bayesian molecular dating method to analyse a dataset of 83 genes from 644 taxa and 52 fossil calibrations to explore the effect of different interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
151
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(183 citation statements)
references
References 92 publications
16
151
4
1
Order By: Relevance
“…The crown age of Lamiales was estimated to be 85.1 Ma (95% HPD, 70.6–99.8 Ma; Fig. ), which is consistent with the divergence time estimation in Barba‐Montoya et al () (95% HPD, 67–101 Ma). The higher core Lamiales diverged from Scrophulariaceae at 65.6 Ma (95% HPD, 51.4–79.4 Ma; Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The crown age of Lamiales was estimated to be 85.1 Ma (95% HPD, 70.6–99.8 Ma; Fig. ), which is consistent with the divergence time estimation in Barba‐Montoya et al () (95% HPD, 67–101 Ma). The higher core Lamiales diverged from Scrophulariaceae at 65.6 Ma (95% HPD, 51.4–79.4 Ma; Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Estimated ages center on 220 Ma for angiosperms (Late Triassic), 150 Ma for eudicots (Late Jurassic), and 132 Ma for Pentapetalae (Hauterivian), comparable to dates of Barba‐Montoya et al . (). The tree implies that colpates were already nearly as diverse as sulcates when they are first observed as fossils in the late Barremian, and more remarkably that colporates were as diverse as colpates, c .…”
Section: Patterns In the Cretaceous Recordmentioning
confidence: 99%
“…Most estimates of the crown angiosperm age fall between 150 and 250 Mya (e.g. 149–256 Mya, Barba‐Montoya, Reis, Schneider, Donoghue, & Yang, ; 162–210 Mya, Magallón, ; 175–240 Mya, Clarke, Warnock, & Donoghue, ; 190–238 Mya, Murat, Armero, Pont, Klopp, & Salse, ; 182–257 Mya, Smith, Beaulieu, & Donoghue, ; 192–251 Mya, Foster et al., ; 158–179 Mya, Wikström, Savolainen, & Chase, ; 167–199 Mya, Bell, Soltis, & Soltis, ). Molecular clocks suggest a Triassic age for crown angiosperms (e.g.…”
Section: The Evolutionary History Of Chinese Angiosperm Flora Might Hmentioning
confidence: 99%
“…In particular, several recent studies have demonstrated that the age of crown angiosperms is >200 million years (e.g. 203 Mya, Barba‐Montoya et al., ; 232 Mya, Beaulieu et al., ; 233 Mya, Brown & Smith, ; 221 Mya, Foster et al., ; 243 Mya, Zanne et al., ; 232 Mya, Zeng et al., ). However, Lu et al.…”
Section: The Evolutionary History Of Chinese Angiosperm Flora Might Hmentioning
confidence: 99%
See 1 more Smart Citation